RESPON PSIKOSOSIAL DAN STRATEGI KOPING PASIEN STROKE DALAM KONTEKS BUDAYA AMBON - Loupatty, Sanci Natalia; Ranimpi, Yulius Yusak; Rayanti, Rosiana Eva (Jurnal Kesehatan, 2019)
Stroke is the dissolution of blood flow to the brain, due to the rupture of blood vessels or blockage of blood vessels to the brain. Stroke results in paralysis, sensory disorders, activity disorders, mental changes such as impaired thinking, awareness, concentration, impaired communication, and emotional disturbance. These changes require the ability of individuals to overcome these problems. This ability is known by the term strategy coping. In general, the known strategy of coping is problem-focused coping and emotion-focused coping. As part of the behavior, psychosocial responses and coping strategies influenced by culture. This study aims to describe the psychosocial response and coping strategy of stroke patients in the context of the culture in Ambon. The method in this study is a qualitative phenomenology approach. Data collection techniques used were in-depth interviews. The participants in this study were four people. Result obtained four themes: (1) physical changes, (2) independence in carrying out activities, (3) psychosocial responses, and (4) coping strategies in a cultural context. Physical changes experienced by participants due to stroke give rise to maladaptive and adaptive psychosocial responses. The coping strategies used to overcome the problem are emotional coping and focus coping issues that are influenced by Ambon culture.